Associations of urine metals and metal mixtures during pregnancy with cord serum vitamin D Levels: A prospective cohort study with repeated measurements of maternal urinary metal concentrations. (October 2021) - Fang, Xingjie; Qu, Jingyu; Huan, Shu; Sun, Xiaojie; Li, Juxiao; Liu, Qi; Jin, Shuna; Xia, Wei; Xu, Shunqing; Wu, Yongning; Li, Jingguang; Zheng, Tongzhang; et al.
Highlights: We observed negative impacts of maternal V/Co/Tl exposure on newborns' vitamin D status. Potential synergism between V and Co and between V and Tl was found. The repeated measurements of metals during pregnancy were conducted. Abstract: Background: Vitamin D deficiency has been associated with the increased risk of many diseases, especially during early life. Exposure to some toxic metals may decrease vitamin D levels in adults and children in previous studies. However, less is known about the associations of maternal metals exposure during pregnancy with newborns' vitamin D status. Objective: We conducted a prospective cohort study to investigate the relationships between urine metals and metal mixtures during pregnancy and newborns' vitamin D status. Methods: Urine samples of 598 pregnant women were collected in each trimester and cord blood samples of newborns were collected at delivery. The concentrations of 20 metals in urine and 25-hydroxyvitamin D [25(OH)D] in cord serum were quantified. Generalized linear models were used to estimate the associations between individual metals and cord serum total 25(OH)D. We applied Bayesian Kernel Machine Regression (BKMR) to evaluate the mixture and interaction effects of urine metals. Results: In individual metals analyses, we reported that a double increase in urine vanadium (V), cobalt (Co), and thallium (Tl) throughout pregnancy was associated with a 9.91% [95% confidence interval (CI): −18.58%, −0.30%], 11.42% (95% CI: −17.73%, −4.63%), and 12.64% (95% CI: −21.44%, −2.86%) decrease in cord serum total 25(OH)D, respectively. Exposures to the three metals during the whole pregnancy were also correlated to increased odds for newborns' vitamin D deficiency (<20 ng/mL) [odds ratio (95% CI): 1.80 (1.05, 3.10) for V, 1.88 (1.25, 2.82) for Co, and 1.90 (1.07, 3.38) for Tl]. BKMR analyses revealed a negative influence of metal mixtures (V+Co+Tl) on neonatal vitamin D status, as well as potential synergism between V and Co and between V and Tl. Conclusions: Our study provides evidence of negative impacts of maternal exposure to V, Co, and Tl during pregnancy on cord serum vitamin D levels at delivery. Potential synergism between V and Co and between V and Tl existed in their associations with cord serum total 25(OH)D.